Efektivitas Penegakan Hukum Lingkungan Administratif Sebagai Upaya Memberantas Pencemaran Akibat Industrial Waste - Afra, Fairuz (Jurnal Media Justitia Nusantara, 2023)
This article discusses the effectiveness of administrative environmental law enforcement as an effort to eradicate pollution caused by industrial waste. The author explains that the problem of environmental pollution due to industrial waste has become a global concern because it can threaten human health and environmental sustainability. However, even though there are laws and regulations governing this matter, there are still many violations committed by the industry. Therefore, enforcement of administrative environmental laws is important to ensure that the industry complies with established regulations and is responsible for the waste it produces. In this article, the author presents several formulations of problems that often occur in society. pollution of the environment to the local area. In conclusion, the authors emphasize that effective administrative environmental law enforcement can help eradicate industrial waste pollution. However, there needs to be a greater and consistent effort by government, industry and society to ensure success in this endeavor.